Artificial Intelligence in Vocational Education: Perspectives and Practices from a Literature Study - Azizah, Nuraini; Hanafi, Ivan; Yusro, Muhammad (Global Synthesis in Education Journal, 2025)
The article presents a literature study synthesizing global perspectives and practices of artificial intelligence (AI) integration in vocational education. It systematically searches Scopus, ERIC, and related databases for publications from 2015 to 2025, yielding 76 peer-reviewed articles. The study employs thematic coding to analyze conceptual foundations, pedagogical approaches, and institutional frameworks. Findings reveal three primary perspectives on AI's role: pedagogical, technological, and organizational. Documented practices such as AI-powered simulators, adaptive learning platforms, and predictive assessment tools. Results demonstrate that AI integration enhances skill acquisition, learner engagement, and personalized instruction while necessitating robust infrastructure and faculty development. The article contributes to vocational education scholarship by mapping current research trends, identifying gaps, and offering actionable recommendations for educators, curriculum designers, and policymakers